Diagnostic Value of Emission Computed Tomography Combined with Computed Tomography for Metastatic Malignant Tumor of Spine. (26th May 2022) - Qin, Feng; Feng, Yapei; Zhang, Panpan; Li, Yuemei; Fan, Weiqiang
Abstract : Objective . To explore the diagnostic value of emission computed tomography (ECT) combined with computed tomography (CT) for metastatic malignant tumor of spine. Methods . By means of retrospective study, a total of 102 patients with extraskeletal primary malignant tumor treated in our hospital from February 2019 to February 2021 were selected as the subjects. All patients had single lesion of the spine, of which 72 were malignant and 30 were benign according to the results of pathological examination. ECT and CT examinations were performed to all patients, and by taking the pathological findings as the gold standard, the sensitivity, specificity, positive predictive value and negative predictive value of ECT, CT, and their combination were calculated, and their efficacy in diagnosing metastatic malignant tumor of spine was analyzed. Results . A total of 68 (94.4%) metastatic malignant spinal tumors were detected by ECT combined with CT, with a detection rate of 100% in breast cancer and lung cancer, 94.1% in liver cancer, and 78.6% in prostate cancer, respectively; the combined diagnosis had a diagnostic sensitivity of 94.4%, specificity of 73.3%, positive predictive value of 89.5%, negative predictive value of 84.6%, and diagnostic accuracy rate of 88.2%, and AUC (95% CI) = 0.839 (0.739–0.939). Conclusion . Combining ECT with CT has a good diagnostic efficacy for metastatic malignant spinal tumors.